‎‎Children in Difficult Situations: Between the Challenges of Reality and the Possibilities of Integration Sociological study/Guercif -Morocco - Douz, Abdelillah (Journal of Humanities & Social Sciences, 2025)
This study aims to highlight the reality of children in difficult situations within the societal framework. This problematic has become a concern and a focus that has emerged amid the social transformations that Morocco has experienced since the beginning of the third millennium. The study seeks to explore the social, economic, educational, and cultural factors contributing to the spread of children in difficult situations. Given the importance and centrality of the child within the broader components of society, and its relevance to the reform and development of the social system hence, the topic is of great importance as it relates to the upbringing of future generations. As such, the issue of children in difficult situations is now at the core of public debate, aiming to strengthen integrated public policies to protect childhood. The study employs a descriptive-analytical approach, which led to several results, the most significant of which is despite growing attention to child-related issues, this category continues to face difficult social, economic, and cultural conditions due to their belonging to poor families. As a result, the study recommends several suggestions, primarily focusing on the importance of investing in the family as a cohesive unit and involving it in all steps and measures taken to protect childhood, while establishing continuous communication channels with it in this regard, as it is a fundamental and indispensable step.